Analisis Faktor-Faktor Yang Mempengaruhi Minat Berwirausaha Dengan Prinsip Syariah Di Kalangan Generasi Z (Studi Kasus Mahasiswa FEB Universitas Jambi): Studi Kasus Mahasiswa FEB Universitas Jambi - Anggreyni, Rizky; Isnaeni, Nurida; Roihan, Muhammad (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2024)
This study aims to analyze whether the religiosity factor, student perception, family environment and technology environment influences the interest of entrepreneurship with sharia principles, given the many violations in the business world. As a research population in this study, students of the Faculty of Economics and Business, Jambi University, class of 2017-2022. The number of research samples used was 96 respondents. The research approach uses a quantitative approach, the research method used is descriptive analysis and case study. The results of this study indicate that: (1) there is a partial influence on religiosity variables, (2) There is no partial influence on student perception variables, family environment and technology environment on entrepreneurial interests with sharia principles, (3) There is a simultaneous influence on religiosity, student perception, family environment and technology environment towards entrepreneurial interest with sharia principles.